Kurikulum Madrasah di Indonesia antara standarisasi nasional dan distingsi keagamaan: Telaah kritis atas arah pengembangan pendidikan - Muhammad Qusairi; Syaifuddin Sabda (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Madrasahs occupy a distinctive position within Indonesia’s national education system as formal educational institutions that are required to comply with national standards while simultaneously preserving their Islamic identity. This dual mandate places the madrasah curriculum within a dynamic negotiation between the demands of national standardization and the need to maintain religious distinctiveness. This study aims to critically examine the construction of the madrasah curriculum in Indonesia in relation to national standardization policies and efforts to sustain the distinctive characteristics of Islamic education. The study employed a qualitative approach using library research. Data were collected from madrasah curriculum policy documents, national education standards, and relevant academic literature. Data were analyzed through critical content analysis involving data reduction, thematic presentation, and critical interpretation. The findings reveal that national standardization plays an important role in ensuring educational quality, equity, accountability, and graduate competitiveness; however, it may also encourage administrative compliance and curricular uniformity when implemented rigidly. Meanwhile, the religious distinctiveness of madrasahs cannot be limited to the inclusion of additional religious subjects but must be integrated into educational goals, academic culture, learning processes, character formation, and the promotion of religious moderation. The study further identifies several major challenges, including the limited integration of religious and general sciences, insufficient teacher capacity for integrative learning, and the predominance of document-oriented curriculum implementation. Therefore, the development of the madrasah curriculum should be directed toward an integrative model that positions national standards as a quality framework while placing religious distinctiveness as the epistemological, pedagogical, and moral foundation of Islamic education. Such a model enables madrasahs to produce graduates who are academically competent, religiously grounded, moderate, adaptable to change, and firmly rooted in Islamic values.